Korelasi antara Keyakinan Masyarakat terhadap Vaksinasi Covid-19 dengan Tingkat Kepuasan Pelayanan Vaksinasi Covid-19 - Mardiana, Lina Aliyani; Julianto, Rasiman; Lutfah, Ika Oktaviyanti (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X, 2023)
Abstract: Vaccination is a way of preventing various kinds of diseases caused by bacteria, viruses or other germs, where people who have been vaccinated become good, protected, not exposed or only experience mild illness when the disease outbreak occurs, as was the case some time ago when there was an outbreak the Covid-19 pandemic, the world community and also the Indonesian people carry out the Covid-19 vaccination simultaneously. Confidence in the success of vaccination encourages people to voluntarily do it and the quality of vaccination services should be in accordance with community expectations. This study aims to determine the correlation between public belief in the Covid-19 vaccination and the level of satisfaction with the Covid-19 vaccination service. This research is a quantitative research using cross sectional method. A sample of 360 people was obtained by distributing online and offline questionnaires. Shows that there is no correlation between public confidence in the Covid-19 vaccination and the level of satisfaction with the Covid-19 vaccination service, the p-value > 0.05 which means Ho is accepted or there is no significant relationship between public belief and service quality. There is no correlation between public confidence in the Covid-19 vaccination and the quality of the Covid-19 vaccination service.